Python Programming Implementation in Food Catalogue Creation Using GUI - Brilian Danuarta; Ifan Prihandi (Journal Collabits, 2025)
In the modern world of programming, the development of user interface (GUI) applications is very important. A simple GUI application can be implemented using the Python programming language and standard modules such as Tkinter, Pandas, and os, as described in this journal. Using this application, users can view the product catalogue, add products to the shopping cart, and make payments. There will be a record of the transaction in an Excel file after the payment is completed. Readers will learn the basic concepts of GUI application development using Python through this practical approach. They will also learn how to use basic features such as file management, user interaction, and data manipulation. This article can serve as a guide for beginners in developing GUI applications using Python.